The potential contribution of innovation systems to socio-ecological transition - Georg Licht; Bettina Peters; Christian Köhler; Franz Schwiebacher (WWWforEurope, 2014)
European countries are currently faced with a variety of challenges, ranging from the new global distribution of economic activity, the diffusion of new, radical technologies to the aging of its population, youth unemployment and the aftermath of the economic and financial crisis. These challenges put the traditional growth model and the policies to foster it under strong pressure. This report summarizes the contributions of the wwwforEurope projects on the definition resp. redefinition of industrial, regional and innovation policy to characterise and stimulate the economies along a new growth path. It is argued that a new growth path needs a new vision on what Europe understands as competitiveness. The report highlights the history and the way forward of European industrial policy. As regional and innovation policy are fully intertwined with industrial policy for a new growth path, it sheds light on these domains as well. For example, the report investigates the role of clusters for the new growth path and the contribution of green innovation, especially in the energy sector, to employment creation. Finally, the report takes a look at the role of SMEs and universities, new players in the new growth model which are normally not included in discussions of competitiveness.
Keywords: O33; J23; L80; C21; C23; 330; Environmental innovation; Social Innovation; Socio-Econological Transition; Europe